Non-conventional solvents in liquid phase microextraction and aqueous biphasic systems - An, Jiwoo; Trujillo-Rodríguez, María J.; Pino, Verónica; Anderson, Jared L. (Journal of Chromatography A, 2017)
•Review describing the use of non-conventional solvents in liquid phase microextraction from 2012 to 2016.•Non-conventional solvents include ionic liquids, magnetic ionic liquids, and deep eutectic solvents.•Dispersive liquid-liquid microextraction and single-drop microextraction approaches are reviewed.•Non-conventional solvents in hollow fiber-liquid phase microextraction are discussed.•Biocompatible solvents in aqueous biphasic systems are reviewed and discussed. The development of rapid, convenient, and high throughput sample preparation approaches such as liquid phase microextraction techniques have been continuously developed over the last decade. More recently, significant attention has been given to the replacement of conventional organic solvents used in liquid phase microextraction techniques in order to reduce toxic waste and to improve selectivity and/or extraction efficiency. With these objectives, non-conventional solvents have been explored in liquid phase microextraction and aqueous biphasic systems. The utilized non-conventional solvents include ionic liquids, magnetic ionic liquids, and deep eutectic solvents. They have been widely used as extraction solvents or additives in various liquid phase microextraction modes including dispersive liquid-liquid microextraction, single-drop microextraction, hollow fiber-liquid phase microextraction, as well as in aqueous biphasic systems. This review provides an overview into the use of non-conventional solvents in these microextraction techniques in the past 5 years (2012–2016). Analytical applications of the techniques are also discussed.